IMPLEMENTATION OF THE GENERAL COST STANDARD POLICY IN THE IMPLEMENTATION OF THE REGIONAL REVENUE AND EXPENDITURE BUDGET OF NORTH MOROWALI REGENCY - Yongki Leonard Pilongo; Irfan Mufti; Dandan Haryono (RADJA PUBLIKA, 2025)
This study aims to analyze the implementation of the General Cost Standard (SBU) policy in the implementation of the Regional Revenue and Expenditure Budget (APBD) of North Morowali Regency using the George C. Edward III policy implementation model which includes communication, resources, disposition, and bureaucratic structure variables. This study uses a descriptive qualitative approach with data collection techniques through in-depth interviews, observations, and documentation studies. Data analysis was conducted using the interactive model of Miles, Huberman, and Saldaña. The results of the study indicate that the implementation of the SBU has not been fully effective. In terms of communication, policy information has not been conveyed evenly, resulting in differences in understanding between regional government agencies (OPDs). In terms of resources, limited staff competency and suboptimal integration of financial information systems have led to errors in budget preparation. In terms of disposition, implementers have resisted, maintaining outdated budget patterns and questioning the adequacy of several cost standards. In terms of bureaucratic structure, fragmentation of authority and weak coordination between units have led to a lack of synchronization in policy implementation. This study concludes that successful implementation of the SBU requires strengthened communication, increased staff capacity, consistent commitment from implementers, and improvements to the bureaucratic structure. These findings provide an empirical contribution to the study of policy implementation within local governments.